No evidence of improvements in inhibitory control with tRNS - Etienne Sallard; Ethan R. Buch; Leonardo G. Cohen; Romain Quentin (NeuroImage: Reports)
Previous work suggests that transcranial random noise stimulation (tRNS) over the prefrontal cortex could influence inhibitory control. Nevertheless, the specific neural mechanisms underlying this proposed effect have not been investigated. Here, we aimed at exploring behavioral and neurophysiological effects of tRNS applied over bilateral inferior frontal gyrus (IFG) on inhibitory control performance during a Go/No-go task (GNG). Nineteen participants performed two tRNS sessions (real and sham) in a double-blind crossover design study. Stimulation was applied over the bilateral IFG during 10 min at 1 mA (range: 1/+1). Resting-state MEG activity was recorded before and after tRNS, and performance on a GNG task was tested after tRNS. Behavioral performance during the GNG task was measured by the false alarm rate (FA), the reaction time in Go (RT Go) and No-go trials (RT FA), and the variability in Go responses (individual coefficient of variability, ICV). Neurophysiological impact of tRNS was assessed using global field power and power spectral density analysis of the MEG recording during the GNG task and the resting-state, respectively. tRNS stimulation did not impact inhibitory control performance. MEG analysis showed significant brain modulations during the resting-state with an increase in power spectral amplitude in beta band (20 Hz) following application of real tRNS. Our results suggest that inhibitory control performance is not modulated by tRNS over the IFG. However, we observed significant modulation of oscillatory brain activity during the resting-state, suggesting that tRNS over bilateral IFG specifically targets the dominant frequency band involved in frontal cortical interactions.